2007
DOI: 10.1021/ja067482k
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Bulkiness Defines the Local Conformations and Dynamics of Natively Unfolded α-Synuclein and Tau

Abstract: Natively unfolded proteins play key roles in normal and pathological biochemical processes. This category of proteins remains, however, beyond the reach of classical structural biology because of their inherent conformational heterogeneity. When confined in weakly aligning media, natively unfolded proteins such as α-synuclein, the major component of abnormal aggregates in the brain of patients with Parkinson's disease, display surprisingly variable NMR dipolar couplings as a function of position along the chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 22 publications
3
70
0
Order By: Relevance
“…66 For the free state of aS, measurements of RDCs have been reported, 45 and have been analyzed in the context of calculations based on ensembles of simulated coillike structures, 67 or on local sequence properties such as side-chain bulkiness. 68 Both of these studies reported a disparity between the calculated and measured RDCs, which was interpreted to reflect the presence of long-range structure within free aS. Here, we have measured RDCs from all three synucleins in stretched polyacrylamide gels ( Figure 7).…”
Section: Residual Dipolar Couplingsmentioning
confidence: 70%
See 1 more Smart Citation
“…66 For the free state of aS, measurements of RDCs have been reported, 45 and have been analyzed in the context of calculations based on ensembles of simulated coillike structures, 67 or on local sequence properties such as side-chain bulkiness. 68 Both of these studies reported a disparity between the calculated and measured RDCs, which was interpreted to reflect the presence of long-range structure within free aS. Here, we have measured RDCs from all three synucleins in stretched polyacrylamide gels ( Figure 7).…”
Section: Residual Dipolar Couplingsmentioning
confidence: 70%
“…44,45 More recently, comparisons of measured and predicted RDCs in free aS have been interpreted to reflect the presence of long-range contacts within the protein. 67,68 Although the idea that long-range contacts within aS may retard the aggregation of the protein has proven popular, a different model proposed that compact conformations of the protein would actually favor amyloid fibril formation. 73 …”
Section: Structural Properties Of Free Asmentioning
confidence: 99%
“…For example, glycine, sampling widely distributed parts of the / space, will induce less order and, therefore, lower RDCs, than preproline/proline pairs, whose conformational sampling are much more restricted. Cho et al 69 have noted recently that averaging the amino acid sidechain bulkiness over a five amino acid window reproduces 1 D NH RDCs along the chain with similar accuracy as the coil model. Apparently, this procedure translates the bulkiness, which is a measure for near neighbor interactions, to the order along the backbone, which is probed by the RDCs.…”
Section: 68mentioning
confidence: 83%
“…42,43 However, the RDC profile also presents residue-specific deviations from the average values that report on the particular conformational space sampled by this residue, mostly reflecting steric restrictions exerted by the neighboring residues. 58 The region encompassing residues 63-70 of USrc presents positive RDCs, with the exception of Gly66 that presents a negative value probably indicating the enhanced local flexibility of this residue compared with the neighboring ones.…”
Section: N-h N Rdcs Of the Unique Domainmentioning
confidence: 98%